-5(2p+4)-12=2(3p+8)

Simple and best practice solution for -5(2p+4)-12=2(3p+8) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -5(2p+4)-12=2(3p+8) equation:



-5(2p+4)-12=2(3p+8)
We move all terms to the left:
-5(2p+4)-12-(2(3p+8))=0
We multiply parentheses
-10p-(2(3p+8))-20-12=0
We calculate terms in parentheses: -(2(3p+8)), so:
2(3p+8)
We multiply parentheses
6p+16
Back to the equation:
-(6p+16)
We add all the numbers together, and all the variables
-10p-(6p+16)-32=0
We get rid of parentheses
-10p-6p-16-32=0
We add all the numbers together, and all the variables
-16p-48=0
We move all terms containing p to the left, all other terms to the right
-16p=48
p=48/-16
p=-3

See similar equations:

| 100x^2-10x+1=0 | | 6(c-5)+9=2+c-23 | | -9m+5m=16-48 | | 11z-13z=8 | | -27=-3r | | 6x+4x=5+15 | | -16-3+29-36=-4-3m-6+4m | | 40p-4+(p+3)=0 | | 4p-3p=-3+12 | | 3x(x+5)=13 | | -5=-3+t | | n-15=-32 | | 8x+13+3x+10=12x-6 | | 2x+6+2x+12=4x+10+2x+6 | | a/5+7=5 | | 3-2(9+2m)=9 | | 15+2j=51 | | 3m+11-2m=-6 | | 4z^2+3z-6=12 | | x(x+1)-195/4=0 | | x(x+2)-195/4=0 | | 5x-3-8x+6=-33 | | 5/2*x-7/4=3/8*x | | 1/10q=3/14 | | 3x=8x2 | | 1/3s+s=12 | | 3b-1/15=4/5 | | A=s2s= | | X-4=y+6 | | 2c-7.5=6.2-3c | | 2(4n+5)+10=-72 | | -7=-5+x/8 |

Equations solver categories